Chapter Movimenti e archivi. Punti fermi e questioni aperte - Musci, Leonardo (Strumenti per la didattica e la ricerca, 2021)
The contribution reflects on the archives of the movements and on the relationship between the characteristics of the productive moment of the documents, their conservative and descriptive destiny and the role of State supervision.